The Weekend Effect in Chronic Hemodialysis Patients, a Single Center Experience (Iranian Journal of Kidney Diseases, 2020)
Introduction. It is not known whether there are any differences in dialysis outcomes of hemodialysis patients on Monday, Wednesday and Friday (MWF) schedule and patients on Tuesday, Thursday and Saturday (TTS) schedules. Patients on TTS schedule who receive one of the treatments on weekends may have worse outcomes compared with patients on MWF schedule as a result of weekend effect. In this study we compared the mortality and clinical performance measures for hemodialysis care, between patients on these two different hemodialysis schedules. Methods. This single center study was conducted on chronic hemodialysis patients above 18 years of age at the time of initiation of hemodialysis who were under thrice weekly hemodialysis treatment for at least 12 months. Mortality and hemodialysis related quality indices were retrospectively compared between patients on MWF or TTS schedules. Results. A total of 188 patients (114 male and 74 female) were included. The mean age of the patients at the start of dialysis was 50.9 ± 18.4 years and median hemodialysis vintage was 60.5 (12 to 369) months. Ninety-nine patients were on MWF schedule and 89 patients were on TTS schedule. More patients on MWF schedule reached the target laboratory values and patients on MWF schedule had a survival advantage compared with patients on TTS schedule. Conclusion. Hemodialysis patients on MWF schedule may receive higher quality of care and may have better outcomes compared with patients on TTS schedule.